Sosialisasi Tentang Peran Prinsip Keadilan Terhadap Hak Dan Kehidupan Siswa Di (Sma N 6 Kota Padang) Dalam Mencegah Perundungan Di Lingkungan Sekolah - Syahputri Julia Anggraini; Zalva Zahlia Kairani; Putri Ryvinasya Lidra; Warida Jasmiza; Muhammad Nazif; Nora Hayati; Rodhia Fadila Herma; Reva Dara Tista; Arya Langgara Zai; Muhammad Chavit Andriansyah; Daffa Benny Nursyid; Ega Zula Gumay; Elwidarifa Marwenny (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Bullying in high schools is a problem that can negatively impact students' social, emotional, and psychological development. One effort to prevent bullying is through socialization of the role of the principle of justice in understanding students' rights and obligations. This activity aims to increase students' awareness and understanding of the importance of implementing the principle of justice in school life to create a safe, comfortable, and respectful environment at State Senior High School 6,  Padang City. The methods used in the socialization activity include delivering material, interactive discussions, and case studies related to bullying. The results of the activity show an increase in students' understanding of rights and obligations and the formation of attitudes of justice, empathy, and social responsibility. Thus, the socialization of the principle of justice plays an important role in preventing bullying and building a positive school culture at State Senior High School 6, Padang City.